Microbicidal activity of N-chlorotaurine in combination with hydrogen peroxide - Mustedanagic, Jasmin; Ximenes, Valdecir Farias [UNESP]; Nagl, Markus (Springer Nature, 2017)
N-chlorotaurine (NCT) and hydrogen peroxide are powerful endogenous antiseptics. In vivo, the reaction between hydrogen peroxide and metal ions leads to the formation of free hydroxyl radicals, which have an increased bactericidal activity. This study examined whether there is an additive antimicrobial effect of NCT combined with hydrogen peroxide. Additionally, it was tested if the additive effect is based on the formation of free radicals. We found by luminometry that, in the presence of H2O2, NCT caused a slow and long-lasting production of singlet oxygen in contrast to HOCl, where this burst occurred instantaneously. Both NCT and hydrogen peroxide (1.0 and 0.1%) demonstrated bactericidal and fungicidal activity. At pH 7.1 and 37 °C, hydrogen peroxide (1%, 294 mM) showed a stronger bactericidal and particularly fungicidal activity than NCT (1%, 55 mM), whereas at pH 4.0 and also in the presence of 5.0% peptone NCT revealed a stronger bactericidal activity. A combination of NCT and hydrogen peroxide led to an increased bactericidal but no increased fungicidal activity compared to both substances alone. The additive effect against bacteria was not removed in the presence of the radical scavengers NaN3, DMSO, or peptone. As a conclusion, NCT and hydrogen peroxide used concurrently interact additive against a range of microorganisms. However, the results of this study suggest that the additive effect of NCT combined with hydrogen peroxide is rather not based on the formation of free radicals.
Keywords: Antimicrobial agent; Hydrogen peroxide; Microbicidal; N-Chlorotaurine; Oxidant; Singlet oxygen